RISK SOCIETY AND GOVERNANCE: CURRENT ISSUES AND CHALLENGES - Halachmi, Arie (The journal of contemporary issues in business and government, 2010)
The paradigm shift from "governing" to "governance" we witness takes place at a time of growing public mistrust in government in general and its use of tax resources in particular. This presents governments and polities with new challenges that have to do with various issues of public accountability, transparency and social responsibility. This paper suggests that, as a result of this shift to governance, more attention must also be given to risk management not only by government but also by other formal and covert participants in the governing process.